Evaluation of the Antimicrobial Activity of Nanostructured Materials of Titanium Dioxide Doped with Silver and/or Copper and Their Effects on Arabidopsis thaliana - Cristina Garcidueñas-Piña; Iliana E. Medina-Ramírez; Plinio Guzmán; Roberto Rico-Martínez; José Francisco Morales-Domínguez; Isidoro Rubio-Franchini (International Journal of Photoenergy)
Nanostructured materials (NSMs) of silver (Ag@TiO2) and copper (TiO2-Cu2+) doped titanium dioxide were synthesized, fully characterized, and evaluated for their antimicrobial efficiency and effects on Arabidopsis thaliana. The NSMs were prepared using an environmentally benign route. The physicochemical properties of the materials were determined with analytical techniques. These materials are active under visible light, exhibit a small size (10–12 nm), are crystalline (anatase), and liberate metal ions (Ag+ and Cu2+) in solution. Microbicide activity was observed in E. coli C600 and S. cerevisiae W303 strains treated with several concentrations of Ag@TiO2 and TiO2-Cu2+, radiated and nonradiated, and after different times. Higher inactivation was achieved with Ag@TiO2 in E. coli, with value of log inactivation of 2.2 with 0.5 mg/mL after 4 h, than in S. cerevisiae, with a log inactivation of 2.6 with 10 mg/mL after 24 h. The impact of these NSMs in plants was evaluated in Arabidopsis thaliana Col-0 strain exposed to such materials at different conditions and concentrations, and physical and biochemical effects were analyzed. Seeds exposed to NSMs did not show effects on germination and growth. However, seedlings treated with these materials modified their growth and their total chlorophyll content.